Mirrors of Salt : 20-24 August 2015, 'Al. I. Cuza' University, Iași, Romania. - Alexianu, Marius. (Archaeopress, 2023)
The study of salt from an anthropological perspective provides a holistic view of its role in the evolution of human communities. Studies from around the world, ranging from prehistory to modern times, are here organized into 6 sections: theory, archaeology, history, ethnography/ ethnoarchaeology/ethnohistory, linguistics, and literature.